Effect of Agitation on the Extraction of Palladium from Spent Industrial Catalyst with Supercritical Carbon Dioxide - FAISAL, MUHAMMAD; ATSUTA, YOICHI; DAIMON, HIROYUKI (Asian Journal of Chemistry, 2010)
The extraction of palladium with supercritical carbon dioxide containing a ligand of tributyl phosphate was studied using a stirred batch reactor. The experiments were conducted at an extraction temperature of 60 ºC and a pressure of 30 MPa. The effects of the use of agitation and ratio of chelating ligand to metal sample on the extraction efficiency at various extraction times were investigated. The mechanism of complex formation of metal-chelating ligand was presented. The results showed that the use of stirred batch reactor could improve the extraction efficiency, especially at a short static extraction time. The chelating ligand to sample ratio and static extraction time also affect the extraction efficiency. High extraction efficiency of 90 % was obtained at the ratio of 10 mL ligand/mg-Pd and 1 h of static extraction time.